Study on causes of delay for government construction project in Kuching, Sarawak - Nurul Asyilah, Romzi (2017)
Delay is a worldwide problem which normally occurs in every project. Delay of the project occurs when a period of time of the completion date is late or postponed. Since the project delayed, the cost of the project will have escalation which will risk the contractors. Instead of getting a benefit from the project, they gain losses. The aim of this study is to identify causes of delay for government construction project in Kuching, Sarawak. This study presents 24 lists of construction delays from research on previous studies. A questionnaire survey was prepared and distributed to 200 companies represented by the client, consultant, and contractor in Kuching, Sarawak. Cronbach’s Alpha and One-Way ANOVA from Statistical Package of Social Science, SPSS are used for reliability test and analysis of data collected from the questionnaire. In order to understand and get a better recommendation for the delays of projects, interviews were conducted with senior professional and expertise parties which experience more than ten years. This study identified most 5 important causes of delay for government construction project which are (1) slow decision making, (2) poor site management and supervision, (3) shortage of labors, (4) changes of scope of work during construction and (5) late in revising and approving design documents. These findings are expected to be a significant contribution to improve the performance of government construction industry in Kuching, Sarawak.